Genetical Modified Organisms (GMO) Products Marketing and the Challenges of Stigmatisation: A Study of Consumers in Enugu State, Nigeria (Nigerian Journal of Cooperative Economics and Management, 2026)
Genetically Modified Organisms (GMOs) technology has been globally recognized as a strategic intervention for achieving food security and nutritional enhancement. Nigeria approved commercial cultivation of genetically modified crops in 2016, with the enactment of the National Biosafety Management Agency (NBMA). Despite this, consumer acceptance remains uneven, especially in the South-East and Enugu state, the core focus of this study. This study examines how stigmatization influences the marketing and consumption of GMO products among consumers in Enugu State. Data were collected from 240 respondents in Enugu metropolis and environs using a structured questionnaire and analyzed with descriptive statistics and logistic regression. While 67.9% of respondents reported awareness of GMOs, only 22.1% had purchased a GMO-labeled product. Stigma was driven mainly by health risk perception, cultural concerns, low trust in regulatory agencies, and negative narratives on social media. Trust in regulatory bodies and accurate awareness significantly increased the likelihood of purchase, whereas stigma reduced it by 77%. The findings suggest that acceptance is constrained more by social perception than by knowledge gaps. To improve uptake, the study recommends clear labeling, community-based communication, and visible engagement by regulatory agencies.
Keywords: Genetically Modified Organisms; Stigmatization; Consumer Behavior; Marketing; Enugu; Nigeria